PROFESSIONALISM OF EDUCATORS IN IMPROVING THE QUALITY OF LEARNING IN ISLAMIC RELIGIOUS EDUCATION - Susanti, Nurma; Syarif, M. Zainul Hasani; Alfaien, Isna Noor (Al-Mubin, 2025)
This research was conducted because of the important role of professional teachers in improving the quality of learning, especially in Islamic Religious Education (PAI) subjects at SMAN 2 Bogor. It was found that the learning methods used were less effective and students lacked attention when studying. The aim of this research is to find out what the professionalism of PAI teachers at SMAN 2 Bogor is like in teaching; and how the role of professional PAI teachers can help improve the quality of PAI learning. This research uses a qualitative method with a descriptive approach. Data was collected through classroom observations, interviews with teachers and school officials, and viewing learning documents. After that, the data is analyzed by simplifying, compiling and drawing conclusions from the information obtained. The research results show that PAI teachers at SMAN 2 Bogor have tried to teach professionally. PAI teachers at SMAN 2 Bogor use effective methods by adapting their classes for this purpose. The teacher's efforts to improve the quality of PAI learning have had a positive impact, although they still need to be improved, especially in terms of creativity and innovation